The effect of ground cover plants in apple orchards on soil-dwelling Collembola - Olena Ewa Niszczak; Jacek Twardowski; Iwona Gruss; Kamila Twardowska; Maria Licznar-Małańczuk (Journal of Plant Protection Research)
Ground cover plants in orchards can effectively improve soil quality. One factor determining soil health is the presence of fauna, including mesofauna, which play a crucial role in soil ecosystems. However, the relationship between ground cover and Collembola assemblages in orchards remains underexplored. This study investigated how different ground cover plants sown in rows of apple trees influence the abundance and diversity of Collembola. Conducted at the Research Station of Wrocław University of Environmental and Life Sciences, Poland, the experiment utilized three cover species: Tagetes patula, Festuca ovina, and Agrostis capillaris, with fallow plots serving as control samples. Soil samples were collected over 2 years (2015–2016) to assess springtails richness and species composition. Results indicated that springtails were significantly more abundant in soils managed with ground cover plants than in conventionally managed fallow stands. Notably, the highest mean Collembola numbers were recorded in strips planted with T. patula and F. ovina. The springtail communities were primarily dominant in each of the treatments by two eudaphic species, Mesaphorura macrochaeta and Hypogastrura assimilis. These findings underscore the importance of cover crops in sustainable agriculture by reducing herbicide reliance, enhancing soil aeration, improving soil fertility through organic matter, and fostering biodiversity of soil biota.